Individuality in language change - Anthonissen, Lynn (Trends in linguistics. Studies and monographs ;, 2021)
Linguists have typically studied language change at the aggregate level of speech communities, yet key mechanisms of change such as analogy and automation operate within the minds of individual language users. Drawing on lifespan data from 50 authors and the intriguing case of the special passives in the history of English, this study addresses three fundamental issues relating to individuality in language change: (i) how variation and change at the individual level interact with change at the community level; (ii) how much innovation and change is possible across the adult lifespan; (iii) and to what extent related linguistic patterns are associated in individual cognition. As one of the first large-scale empirical studies to systematically link individual- and community-based perspectives in language change, this volume breaks new ground in our understanding of language as a complex adaptive system.